EFFECT OF STEM DIAMETER, MEDIA TYPE AND LIGHT INTENSITY ON THE GROWTH OF MEDICINAL PLANT OF SCREW TREE/KAYU ULES (Helicteres isora Linn.) - Pamungkas, Dani; Umroni, Aziz; Adi Prasetyo, Nurhuda (Association of Indonesian Forestry and Environment Researchers and Technicians, 2021)
Screw tree (Helicteres isora Linn.) known as kayu ules is a shrub species (Fam: Malvaceae) with 1.5–4 m in height and with multi-main trunks up to 9–12. In Indonesia, kayu ules has been used as a traditional medicine, known as jamu, and has been commercialized. In order to cultivate this species, vegetative propagation is likely promising compared to the generative propagation since seed viability is low and cannot be stored for long period. Nevertheless, there is a lack of information on which diameter classes, media types and light intensities would give the best result for vegetative propagation. This research aimed to obtain information on which diameter classes and media type suitable for kayu ules stem cutting propagation the light intensity degree for the growth of kayu ules seedlings. Three diameter classes and four media types were employed in a complete random design under the greenhouse environment. Three months old good quality vegetatively-propagated seedlings were transplanted under two light intensities (under transparent canopy and shading net). Result shows that considering diameter classes and media type in kayu ules stem cutting propagation, it had improved the survival of the stem cutting. Diameter class I was the best grown in media type 3 with 46.67 ± 12.2 % of survival rate, diameter class II was best grown in media type 2 with 38.67 ± 11.6 % of survival rate, whereas diameter class III was best grown in media type 4 with 52 ± 6.9 % of survival rate.